FACTORS ANALYSIS OF DRIVE PURCHASE DECISION ON MAPANGET GRIYA INDAH 4 - Amelia, Nur Ayu Rezky; Massie, James D.D; Pandowo, Merinda . (Universitas Sam Ratulangi, 2017)
Abstract: House as one of the human needs besides food and clothing. Every human needs a house for shelter and also a meeting place with family every day. Nowadays in North Sulawesi province, many estates were built. One of the most preferred by the people of Manado to buy a house is Mapanget Griya Indah 4. This study aims to analyze the factors that drive customer purchase decisions in the house at Mapanget Griya Indah 4. The population of this study is people who buy a house or are already living in Mapanget Griya Indah 4, with sample 100 respondents. The objective in this research is to analyze the factors that drive purchase decision of Mapanget Griya Indah 4. The method used in this research is a quantitative method by spread the questionnaires to obtain primary data. In this study the results and conclusions found to explain that there are sixteen variables that drive customer purchase decision, which then formed the six factors and there are four variables that do not significantly influence the purchasing decisions in Mapanget Griya Indah 4. Four variables were not significantly influence the purchasing decisions in Mapanget Griya Indah 4 are security, quality of the area, views & roads and price.Â Keywords: customer purchase decisionÂ Â